Screening forage and browse legumes germplasm to nutrient stresses: III. Tolerance of Sesbania to aluminium and low phosphorus in soils and nutrient solution - Mugwira, L.M.; Haque, I. (Informa UK Limited, 1993)
Sesbania, particularly S. sesban species, grow naturally in many parts of Africa where they form natural browse. Productivity of Sesbania as animal feed is widely limited by soil acidity and low In this study, eighteen ILCA accessions of S. sesban and two of S. goetzei, all but two from Africa, were evaluated for tolerance to acidity and low P on two Ethiopian soils as well as their tolerance to Al and response to P in nutrient solutions. The treatments were O and 4000 mg CaCO3/kg (PH 4.8 and 5.6) in combination with O and 37.5 mg P/kg on a Soddo Nitosol. On the chencha clay loam with 77 percent Al saturation, the PH values were 4.1 (unlimed) and 5.9 (limed) in combination with 0 and 25 mg P/kg on the unlimed soil plus 37.5 mg/P/kg on the limed soil. Treatments applied to the nutrient solutions were 0, 3, and 6 ppm Al in combination with 155 and 6200 PPm P as KH2p04. On the Soddo soil, Sesbania responded primarily to P which increased average shoot growth by 171 to 822 percent with low response (6.5 percent) to lime which did not significantly differ among the accessions. On the chencha soil, the Sesbania were highly responsive to lime and P which increased shoot growth by 129 to 425 percent, and 100 to 492 percent respectively. The Sesbania varied in their tolerance to Al which gave shoot yield reductions of 18 to 69 percent with 3 PPm and 33 to 84 percent with 6 PPm Al at low Increasing P level to 6200 PPm greatly alleviated the deleterious effects of Al to such an extent that only one accession had growth reduction greater than 50 percent at 3 PPm Al. The accessions from Uganda showed similar high performance in soils and nutrient solutions, but there was more divergence in the performance of the accessions from each of the other countries, Kenya, Ethiopia, and Tanzania.